ANALISIS PERBANDINGAN EMISI DARI PERBEDAAN METODE PENGGORENGAN KERIPIK PISANG DI LAMPUNG DENGAN METODE LCA (LIFE CYCLE ASSESSMENT) - Perdana, Rechal; Ismayana, Andes; Yani, Moh (Department of Agroindustrial Technology, Bogor Agricultural University, 2024)
Banana chip processing in Lampung province uses two different frying methods, namely conventional frying and vacuum frying. The objective of this study was to compare the number of impact emissions generated from the banana chip production process in banana chip agro-industries in Lampung. This research was conducted based on the Life Cycle Assessment (LCA) method to assess the environmental impact emissions from the banana chip industry in Lampung, focusing on the impacts of Global Warming Potential (GWP), Acidification Potential (AP) and Eutrophication Potential (EP) with a function unit of 250 g/pack. Analysis using SimaPro 9.4.2 software. Analysis using the CML-IA Baseline method shows that the banana chip industry has a significant environmental impact with the largest impact by the industry, where the conventional frying method produces a GWP impact of 1.16 kg CO2 eq/package, EP 2.08E-2 kg PO4 eq/package and AP 3.6E-3 kg SO2 eq/package, while in the vacuum frying method, the GWP is 6.3E-1 kg CO2 eq/package, AP 2.3E-3 kg SO2 eq/package and EP 6,1E-3 kg PO4 eq/package. The calculated normalization data shows that the total impact of producing banana chips per package in conventional frying is 1.9E-12 person equivalent/package with the frying stage contributing 85.45% and in vacuum frying is 6.7E-13 person equivalent/package with the frying stage contributing 77.70%. The resulting emission impact value shows that the emission impact of conventional frying is higher than the emission impact of vacuum frying. However, an economic and social assessment of both frying methods needs to be done to see the sustainability index of both. Keywords: banana chips, LCA, simapro, vacuum frying